2018
DOI: 10.1021/acsanm.8b02139
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Driven Fabrication of Catalytically Reactive Rhodium Nanoplates

Abstract: Here we present the use of a well-known materials binding peptide for the generation of highly catalytically reactive Rh nanoplates. To this end, the A3 peptide, originally isolated with affinity for Ag, but with known abilities to bind Au, was used to generate Rh nanomaterials in solution. Rh was selected due to its established catalytic reactivity for numerous reactions; however, the preparation of materials of this composition typically requires high reaction temperatures and potentially caustic conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…This also may play a role in the slower reactivity of the alkyne, whereby it is adsorbed to the particle surface for longer times. Such results are consistent with prior studies that demonstrated similar alkyne effects. , …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This also may play a role in the slower reactivity of the alkyne, whereby it is adsorbed to the particle surface for longer times. Such results are consistent with prior studies that demonstrated similar alkyne effects. , …”
Section: Resultssupporting
confidence: 93%
“…For the reaction, the BNPs were bubbled in solution with H 2 gas, after which the olefinic substrate was added. Aliquots were removed from the reaction at selected time points and quantified by GC. Figure a presents the GC analysis for the hydrogenation of allyl alcohol to 1-propanol catalyzed by the Pt 80 Au 20 -AuBP2 materials. As is evident, clear separation of the starting material and product was achieved with no evidence of isomer formation.…”
Section: Resultsmentioning
confidence: 99%
“…Such reactivity suggests that the BiVO 4 /BiOBr/Pd photocatalyst can achieve semihydrogenation of alkynes to alkene intermediates. This degree of alkyne reactivity likely arises from a preferential adsorption or slower desorption of alkynes over alkenes from the material surface, which has been noted in other systems. Such differences in adsorption/desorption rates can account for the observation that there is very little hydrogenation of the alkene intermediate until the alkyne has been completely consumed. This is achieved even though the rate for hydrogenation of the alkene in the absence of alkyne was substantially greater than the alkyne semihydrogenation rate.…”
Section: Resultsmentioning
confidence: 93%
“…Palladium catalysts have been popularly used for hydrogenation, exceeding the reputation of other metal catalysts such as platinum and rhodium. One of the reasons for that is their lower metal hydrogen bonding energy compared to those of both Pt and Rh . The classical palladium on carbon (Pd/C) is well known for efficient hydrogenation of organic compounds possessing various reducible functionalities .…”
Section: Introductionmentioning
confidence: 99%